2022
DOI: 10.1111/1744-7917.13085
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐producing tomato plants have a direct negative effect on the zoophytophagous biological control agent Orius sauteri

Abstract: Orius sauteri (Poppius) (Hemiptera: Anthocoridae) is often used for biological control of small arthropod pests in greenhouse vegetable production systems in Asia. In addition to feeding on arthropod prey, O. sauteri consumes small quantities of plant material. Previous studies demonstrated that tomato plant chemistry confers antixenosis resistance to phloem-feeding whiteflies, but the potential nontarget effects of phytochemicals on the beneficial predator O. sauteri are unknown. Comparison of O. sauteri conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In addition, female bugs deposited significantly fewer eggs on P. absoluta -resistant genotypes than on susceptible plants. Yang et al (2022) [ 34 ] reported similar results for O. sauteri on whitefly-resistant genotypes, suggesting that phytochemicals have a direct adverse effect on a beneficial species and phytochemical-mediated resistance can affect non-target insects. Additionally, they suggested that phytochemical-mediated resistance has a potential ecological impact.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, female bugs deposited significantly fewer eggs on P. absoluta -resistant genotypes than on susceptible plants. Yang et al (2022) [ 34 ] reported similar results for O. sauteri on whitefly-resistant genotypes, suggesting that phytochemicals have a direct adverse effect on a beneficial species and phytochemical-mediated resistance can affect non-target insects. Additionally, they suggested that phytochemical-mediated resistance has a potential ecological impact.…”
Section: Discussionmentioning
confidence: 90%
“…Plant chemical composition may be particularly important to the performance of omnivorous consumers that feed on both prey and plant materials. Such omnivores may exhibit retarded development and impaired survival and fecundity when they feed on defended plants [ 34 , 43 ]. In addition, the efficacy of biological control agents may be inferior on crop plants that are defended by glandular trichomes [ 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, an interesting perspective relies on the use of agricultural wastes as flavonoids' source material under the frame of a circular economy approach, once field experiments and evaluations on features such as environmental fate and target specificity would have ensured their safe use [229]. Flavonoids can have indeed a harmful effect on nontarget beneficial species, as observed on the zoophytophagous generalist predator Orius sauteri, a biological control agent of whiteflies, which showed a reduced oviposition, nymphal survival, and development on flavonoids-producing tomatoes [233]. Several studies also reported the phagostimulant or neutral activity of flavonoids in dependence of the insect species considered and of the molecule and dosage selected [228,234].…”
Section: Flavonoids Modulate Behavior and Life History Traits Of Inse...mentioning
confidence: 99%